RANCANG BANGUN ALAT SINKRONISASI PEMBANGKIT LISTRIK TENAGA SURYA DENGAN JARINGAN PLN ON GRID MENGGUNAKAN ARDUINO NANO - Aristoteles Narang (2024)
Electrical energy has become a daily necessity for people around the world, especially Indonesia. In 2022, the State Electricity Company (PLN) provided electrical energy using power plants that predominantly used coal with a percentage of 67.21%, while the use of renewable energy was only 12.2%. Therefore, the government issued PP No. 79 of 2014 concerning Renewable Energy Policy where the target of the energy mix in 2025 is at least 23%. To increase the percentage of renewable energy can use Solar Power Plants that are integrated with PLN. The Solar Panel in this study will be paralleled with PLN using Arduino Nano. This research uses ZMPT101B sensor, frequency sensor, and phase angle sensor to see the parameter difference between PLTS and PLN. Testing is done by comparing sensor readings with measuring instruments, namely multimeters and oscilloscopes and compared with synchronization standards whether it can synchronize. The data obtained is a voltage difference of 5 Volts ± 0.31%, a frequency difference of 0.1 Hz ± 1.42%, and a phase angle difference of 1.35 ° ± 2.99%. The data when compared to the synchronization standard is small and falls into the standard. The synchronizer designed in this study is feasible for synchronization.